Urban farming and food - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Ham Onsando, a restaurant owner and member of the Global Food Safety organisation, describes risks from dirty irrigation water used in urban farming, and other food risks facing urban consumers.